Análise da ocorrências de quedas em pacientes admitidos em unidades de cuidados críticos - Bárbara Cristina Dias Giaquinto (2021)
Falls are one of the most frequent adverse events in tertiary care and their occurrence causes sometimes irreversible damage to patients and burdens to their families, institutions and health professionals. For patients admitted to critical care units such as the operating room, emergency room and intensive care unit, data on falls, post-fall management, complications and in-hospital outcomes are not yet consolidated for a directive and safe clinical practice. This study aimed to analyze the occurrence of falls in adult patients admitted to critical care units. This is a quantitative and descriptive study carried out in five general and large hospitals in Belo Horizonte. The collection occurred through consultation of 117 medical records of adult patients who suffered falls in critical care units and whose event was reported to the Center for Patient Safety of the institutions from April 2013 to December 2019. Sociodemographic and clinical data, data related to the fall event, complications and in-hospital outcomes were investigated. The variables were described by means of frequency, percentages and measures of central tendency. There was a predominance of males (59.83%), living without a partner (35.04%) and in the age group of 60 years or older (54.70%). External causes (25.64%), hypertension (47.00%) and alcoholism (23.08%) were the most frequent clinical characteristics. Falls were more frequent in the early morning period (27.35%), in the Emergency Room (76.07%) and most patients were accommodated on a stretcher (36.75%) or in bed/bed (29.91%). As for the degree of injury at the time of the fall, the 'no injury' category predominated (43.59%). Almost half of the patients (47.86%) were not assessed for fall prediction on admission and 47.01% underwent assessment on the day of the event. The Morse Fall Scale was applied in 26.50% of these patients. As for risk factors, 47.86% had psychomotor agitation/acute confusions and 16.24% cognitive alterations, 18.80% were under chemical restraint and 11.11% with physical restraint of the upper limbs. After the fall, the most indicated imaging exam was the skull tomography (19.06%). The most frequent complications from a fall were blunt force injuries (13.68%), abrasions (10.26%), and mild traumatic brain injury (9.40%). More than half were discharged (52.14%) and 4.27% died as a result of the fall. Falls were more frequent in emergency rooms and in elderly people. The use of prediction scales is not frequent in the admission of patients. It was observed the need for additional propedeutics after a fall and the fall-related outcome is sometimes irreversible. It is notorious the need to rethink the practice and seek better strategies for fall prevention aiming at a more qualified and safer care for critically ill patients.